Overview of Ubicomp Research Based on Scientific Publications - Silva, Thiago H.; Celes, Clayson S. F. de S.; Mota, Vinícius F. S.; Loureiro, Antonio A. F. (Anais do Simpósio Brasileiro de Computação Ubíqua e Pervasiva (SBCUP), 2012)
This paper provides an overview and analysis of recent ubiquitous computing research performed internationally and in Brazil. The contributions are twofold. First, we extracted useful information from a dataset of papers published in top conferences focused on ubicomp, for instance, representativeness of authors and institutions, and communities’ formation. Second, we analyzed all papers published between 2010 and 2011 in all top international conferences, creating a taxonomy of recent ubicomp research performed internationally. Next, we mapped SBCUP papers on this taxonomy. With that, we were able to compare the international and national research.